Disclosure of Risk and Underpricing in Initial Public Offerings in the Indonesian Capital Market - Ariyani, Vivi; Gumanti, Tatang Ary; Sukoco, Y. Djoko (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study tests whether the risk factors disclosed in the prospectus are able to explain the variation in underpricing. The data used in this study uses cross-sectional data on 364 companies that conducted initial public offerings on the Indonesia Stock Exchange for the period 2018 to 2024. The research results risk disclosure is measured using two methods, namely based on rating risk and risk as determined by the capital market regulatory agency in Indonesia, which produces consistent findings. In this case, it explains that risk disclosure by companies conducting IPOs, both the risks that are being faced and those that will be faced by the issuing company, is able to reduce the level of underpricing.